HLA-B27-associated acute anterior uveitis in the University Referral Centre in North Thailand: Clinical presentation and visual prognosis - K. Pathanapitoon (2018)
Background: Acute anterior uveitis (AAU) is the most frequent type of uveitis encountered in the west. Although human leucocyte antigen (HLA)-B27-associated ankylosing spondylitis was reported in South East Asia, it is not known whether HLA-B27-associated ocular disease is prevalent in Thailand. Methods: A prospective study of 100 unrelated blood donors and 121 consecutive patients with AAU was carried out. All people underwent HLA-B27 typing and full ocular examination. Radiological examination of the sacroiliac joints was conducted in patients with low back pain or arthralgias. Results: The prevalence of HLA-B27 was 10% among the blood donors in contrast with 44% in the AAU group (p<0.001). The clinical characteristics of HLA-B27-associated AAU were similar to those published throughout the world (unilaterality in 74%, hypopyon in 31%, recurrent AAU in 64%). However, the increased intraocular pressure (IOP) was more common in the HLA-B-27-negative group (p = 0.03) than in their HLA-B27-positive counterparts. At least 15% of the HLA B27-positive group had radiological signs of ankylosing spondylitis. Conclusion: The prevalence of HLA-B27 in the population without uveitis in Thailand is about 10% and clinical characteristics of HLA-B27-positive AAU are similar to those reported in the west. In contrast with earlier reports, HLA-B27-negative AAU in Thailand was associated with increased IOP and should be further studied.